Synthesis of 2-(2,3,4-trimethoxyphenyl)-1-(substituted-phenyl)acrylonitriles: In vitro anticancer activity against MCF-7, PC-3 and A2780 cancer cell lines - Özen, Furkan; Tekin, Suat; Koran, Kenan; Sandal, Süleyman; Görgülü, Ahmet Orhan (My University, 2016)
A series of 2-(2,3,4-trimethoxyphenyl)-1-(substituted-phenyl)acrylonitrile (2–9) were designed and synthesized to develop new cancer drugs. The structures of synthesized compounds 2–9 were described by using melting point, mass (MALDI-TOF-MS), FT-IR, elemental analysis, 1H, 13C, 13C-APT and 2D NMR spectroscopy. The in vitro anticancer activities of 2–9 against human breast cancer (MCF-7), human prostate cancer (PC-3) and human ovarian cancer cells (A2780) were investigated by [3-(4,5-dimethylthiazol)-2-yl]-2,5-diphenyl-2H-tetrazolium bromide] (MTT) assay method. Additionally, the LogIC50 values of these compounds on A2780, MCF-7 and PC-3 cell lines were calculated by using inhibition % values by the GraphPad Prism 6 program on a computer. The results indicated that these compounds have high anticancer activity against MCF-7, PC-3 and A2780 cell lines (especially A2780 cell lines, p < 0.05).
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Phenylacrylonitrile derivatives; Human ovarian cancer cell; MCF-7; Anticancer evaluation; PC-3